Hepatopulmonary Syndrome with Right-to-left Shunt in Cirrhotic Patients Using Macro-Aggregated Albumin Lung Perfusion Scan: Comparison with Contrast Echocardiography and Association with Clinical Data / Sirotik Hastalardaki Sag-Sol Sant ile Iliskili Hepatopulmoner Sendromun Tanisinda Makro-Agregant Albumin Akciger Perfuzyon Sintigrafisinin Kontrast Ekokardiyografi ile Karsilastirilmasi ve Klinik Veriler ile Iliskisi - Alipour, Zeynab; Armin, Abbas; Mohamadi, Sudabeh; Tabib, Seyed Masoud; Azizmohammadi, Zahra; Gholamrezanezhad, Ali; Assadi, Majid (Molecular imaging and radionuclide therapy, 2020)
Objectives: The diagnosis of hepatopulmonary syndrome (HPS) which is a common complication in cirrhotic patients is still subject to debate. This study investigated the association of clinical findings with HPS in cirrhotic patients using macro-aggregated albumin lung perfusion scan ([.sup.99m]Tc-MAA lung scintigraphy). In addition, comparison between [.sup.99m]Tc-MAA lung scintigraphy and contrast echocardiography (CEE) in detection of HPS was also performed. Methods: In this study, 27 patients with cirrhosis underwent [.sup.99m]Tc-MAA lung scintigraphy and contrast echocardiography comparison CEE and the frequency of HPS was assessed in them and also was compared across the other variables. Results: The [.sup.99m]Tc-MAA lung scintigraphy showed HPS in 13 patients (48.1%) while CEE demonstrated HPS in 5 patients with cirrhosis (18.51%). HPS was mild in 40.74% (11/27) of the patients, and severe in only 2 patients. There was no relationship between gender, disease duration, having diagnosis of disease previously, pulmonary symptoms and Child-Pugh score variations and HPS (p>0.05). Comparison of hemodynamic indices, arterial blood gas analysis and laboratory indices between patients with and without HPS was also non-significant (p value >0.05). Among coagulation factors assessed in cirrhotic patients, we found only significant correlation between HPS and prothrombin time (p<0.05). Conclusion: HPS, particularly its mild form, is noted in a great number of patients with cirrhosis using [.sup.99m]Tc-MAA lung scintigraphy. Because of its technical ease, and possibility to obtain objective quantitative information, [.sup.99m]Tc-MAA lung scintigraphy can be complementary to other diagnostic methods in the evaluation of HPS assessment, although additional studies are needed. Keywords: Hepatopulmonary syndrome, cirrhosis, macro-aggregated albumin lung perfusion scan, contrast echocardiography Amac: Sirotik hastalarda sik gorulen bir komplikasyon olan hepatopulmoner sendromun (HPS) tanisi halen tartismaya aciktir. Bu calismada, makroagregat albumin akciger perfuzyon sintigrafisi ([.sup.99m]Tc-MAA akciger sintigrafisi) kullanilarak sirotik hastalarda klinik bulgularla HPS'nin iliskisi arastirilmistir. Ayrica, HPS'nin saptanmasinda [.sup.99m]Tc-MAA akciger sintigrafisi ile kontrast ekokardiyografi (KE) karsilastirilmistir. Yontem: Bu calismada, sirozlu 27 hastada [.sup.99m]Tc-MAA akciger sintigrafisi ve KE karsilastirildi ve HPS sikligi degerlendirildi. Ayrica HPS'nin sikligi ile diger degiskenler arasindaki iliski arastirildi. Bulgular: [.sup.99m]Tc-MAA akciger sintigrafisi 13 sirozlu hastada (%48,1) HPS'nin varligini gosterirken, KE 5 sirozlu hastada (%18,51) gosterdi. HPS hastalarin %40,74'inde (11/27) hafif, sadece 2 hastada siddetliydi. Cinsiyet, hastalik suresi, hastalik gecmisi, akciger semptomlari ve Child skoru ile HPS arasinda herhangi bir iliski yoktu (p>0,05). Hemodinamik indeksler, arteriyel kan gazi analizi ve laboratuvar indeksleri acisindan HPS'li hastalar ve HPS'li olmayan hastalar arasinda fark gorulmedi (p>0,05). Sirotik hastalarda degerlendirilen koagulasyon faktorleri arasinda, sadece HPS ve protrombin zamani arasinda anlamli bir korelasyon bulundu (p<0,05). Sonuc: [.sup.99m]Tc-MAA akciger sintigrafisi ile cok sayida sirozlu hastada HPS'nin ozellikle hafif formu saptandi. Teknik kolayligi ve objektif kantitatif bilgi edinme olasiligi nedeniyle, [.sup.99m]Tc-MAA akciger sintigrafisi HPS'nin degerlendirilmesinde diger tani yontemlerini tamamlayici olabilir, ancak ek calismalara ihtiyac vardir. Anahtar kelimeler: Hepatopulmoner sendrom, siroz, makroagregat albumin akciger perfuzyon sintigrafisi, kontrast ekokardiyografisi